Proteomics of human teeth and saliva - Jágr, M; Eckhardt, A; Pataridis, S; Broukal, Z; Dušková, J; Mikšík, I (Physiological research, 2014)
Teeth have been a focus of interest for many centuries--due to medical problems with them. They are the hardest part of the human body and are composed of three mineralized parts--enamel, dentin and cementum, together with the soft pulp. However, saliva also has a significant impact on tooth quality. Proteomic research of human teeth is now accelerating, and it includes all parts of the tooth. Some methodological problems still need to be overcome in this research field--mainly connected with calcified tissues. This review will provide an overview of the current state of research with focus on the individual parts of the tooth and pellicle layer as well as saliva. These proteomic results can help not only stomatology in terms of early diagnosis, identifying risk factors, and systematic control.
Keywords: proteom; Tooth; tkáňová distribuce; Gene Expression Profiling; proteomika; Tissue Distribution; sliny; Proteomics; lidé; zuby; Proteome; stanovení celkové genové exprese; Saliva; Humans